Resilent by Design: 4A-Driven Sustainable Tourism Recovery in Tanjung Lesung Special Economic Zone (SEZ) - Raga, Ridha Azka; Pertiwi, Husna Putri; Suryantari, Yulita; Salim, Mufid (SAFE-Network, 2025)
Following the 2018 tsunami and the COVID-19 pandemic, Tanjung Lesung, Indonesia's first Tourism Special Economic Zone (SEZ) has faced profound challenges. These crises caused a sharp decline in tourist visits, safety concerns, and damage to the area’s reputation, slowing local economic growth and diminishing the SEZ's contributions to the national economy. These events underscored the vulnerability of tourism systems and raised concerns regarding achieving sustainable tourism objectives. This study examines the 4A framework (Attractions, Accessibility, Amenities, and Ancillary Services) to explore its role in fostering resilience and sustainability in the tourism industry. Key Penta-helix stakeholders were interviewed in-depth using a qualitative descriptive technique from both public and private sectors. This study shows that rejuvenating tourism in Tanjung Lesung SEZ depends on including the 4A framework. Results offer practical suggestions such as encouraging sustainable economic growth and good work for local communities (SDGs 1 and SDGs 8), improving safety and disaster risk reduction, and supporting action to mitigate climate change (SDGs 13). This study highlights the importance of multi-stakeholder cooperation as well as the 4A framework in reaching sustainable tourist development in a post-crisis context.